Investigating the role of the Dendritic Cell Immunoactivating Receptor in the Immune Response during Pneumocystis murina - Mthembu, Nontobeko F (Department of Clinical Laboratory Sciences, 2020)
Pneumocystis jirovecii causes fungal pneumonia in immunocompromised patients and can be fatal if left untreated. The global mortality rate is estimated to be over 200 000 in AIDS patients. In non-AIDS patients there is an estimated mortality rate of 50 000 cases. This rate is increasing in developed countries, attributed to an increase in disorders which require immunotherapy. These include hematologic malignancies, organ transplant, inflammatory disorders and pre-existing lung disease. Immediate immunity is initiated by receptors that recognize pathogen associated molecular patterns on the surface of pathogenic fungi. Specifically, C-type lectin receptors (CLRs) have been shown to be the principal initiators of innate immune response during fungal infection. Limited studies have focused on the role of CLRs in Pneumocystis infection. Dectin1and Mincle have been shown to recognise Pneumocystis surface antigens with Dectin-1 recognizing β-glucans on the Pneumocystis cell wall leading to an effective immune response. However, the role of a newly described CLR, the Dendritic Cell Immunoactivating Receptor (DCAR) remains undefined. For this reason, we investigated the potential role of this receptor in a mouse model of Pneumocystis murina infection. Wild type and DCAR-deficient C57BL/6 mice were infected with P. murina organisms via intratracheal instillation. Fungal burden was measured in the lung using quantitative Polymerase Chain Reaction. DCAR-deficient mice had a significantly reduced burden compared to wild type mice at Day 7 and 14 post-infection. To identify the immune components involved in pathogen clearance in these mice we measured cellular recruitment and cytokine production at both early (48 hours) and late (7, 14 and 21 days) time points. Flow cytometry analysis showed an increase in alveolar macrophage, dendritic cells, inflammatory monocytes, eosinophils and T cell recruitment to the lung. While ELISA showed increased levels of IL-1β and IFN-γ at 48 hours, and later on in infection IL-1β and IL-12p40 levels were also elevated. Histology analysis determined the localization of the recruited cells, and v interestingly showed an increase in mucus production at day 21 in DCARdeficient mice. In conclusion, we have identified DCAR deficiency as a potential driver of protective immunity in mice during P. murina infection. This may be associated with increased levels of IL-1β in DCAR-deficient mice. Furthermore, DCAR may also be important in adaptive inflammatory response regulation, as DCAR-deficient mice have increased cellular recruitment and mucus production later in infection. The mechanism by which the deletion of this receptor affords these mice the ability to efficiently clear P. murina remains to be determined.